Relationship of Knowledge and Attitudes on Vitamin D Status in Active Smokers - Amelia Lorensia; Marthy Meliana Ariyanti Jalmav; Eva Amilia; Amirah Dyandra Sybil (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2026)
Systemic exposure to cigarette smoke adversely affects the metabolism of vitamin D. An individual's understanding of smoking can significantly shape their attitude towards it. This study sought to explore the correlation between knowledge and attitudes regarding vitamin D levels among active smokers. This type of research is cross sectional in the Mejoyo area, carried out in April-July 2023. Respondents were male active smokers who and not having allergies to fish, eggs and milk, by using a purposive sampling technique. Respondents were filling in demographic data, filling out a knowledge and attitude questionnaire, as well as a vitamin D status questionnaire. The relationship between knowledge, attitudes and vitamin D status was tested using chi-square. The total number of respondents was 124 people. Most respondents had low level of knowledge (82.40%) and medium attitude level (92.80%). The risk of vitamin D deficiency was 54.80% and no risk of vitamin D deficiency was 45.20%. With the chi-square test, there was no significant relationship between knowledge (P=0.173) and attitude (P=0.960) related to vitamin D and the risk of vitamin D deficiency. Therefore, further research is needed on the factors that influence vitamin D by increasing knowledge and attitudes.